Pengaruh Faktor Intrinsik Terhadap Prestasi Kerja (Kasus Pada Agen PT. Asuransi Jiwasraya (Persero) Cabang Pekanbaru) - Mariaty, Christine; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
PT. Insurance Jiwasraya (Persero) Branch Pekanbaru, which is a company engaged in insurance services, which in running the company's business activities in offering and selling insurance policies to the public cann’t be separated from the role of insurance agents. The efforts made by the company is focused on factors intrinsic conditions of the job itself, where intrinsic factor is the motivation that comes from within that can improve agent performance High motivation derived from the agent, then this is a guarantee for the company's success in achieving its objectives.The purpose of this study was to analyze the influence of intrinsic factors on job performance agents. This study uses quantitative descriptive correlational technique in which the data were collected through questionnaire method against 78 respondents. Then the simple linear regression analysis of the data obtained.Results of research and hypothesis testing shows that there is a significant positive relationship between intrinsic factor and agent performance in PT. Insurance Jiwasraya (Persero) Branch Pekanbaru. Through test the coefficient of determination in this study proved that the intrinsic factors affecting agent performance by 44%, and the remaining 56 % is influenced by other factors .Keywords : Intrinsic Factor , Job Performance, Motivation.